It's my turn, Smudge! - Moss, Miriam; Chapman, Lynne, 1960- (London : Gullane Children's Books, 2001)
Smudge has trouble sharing her new fishing net.
Keywords: Sharing -- Fiction; Children's stories -- Pictorial works